The Implementation of Demonstration Method to Increase Learning Interest and Outcomes of the Second Grader As-Shakireen School, Thailand - Kamalia Fikri; Reta Kusuma Wardani; Ulyanada . (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2018)
This study aimed to increase the interest and learning outcomes of English through Demonstration Method in class II students of As-Shakireen Primary School, Thailand. This research was a classroom action research. Data collection techniques were carried out by means of observation, interest scale, and tests. Data analysis techniques were carried out by means of qualitative and quantitative descriptive. Increased interest and English learning outcomes with Demonstration methods carried out from pre-cycle activities, cycle 1 consisting of stages of planning, acting, observation, and reflection. Based on the results of data analysis, it showed the scale of student interest from pre-cycle to cycle with the use of demonstration method has increased. While student learning outcomes also experience an increase as indicated by the average value of students and the average students who exceed the minimum criteria. So that the demonstration method implemented can increase the interest and learning outcomes of class II students in English subjects at As-Shakireen primary school. Keywords: demonstration method, learning interest, learning outcomes